Penerapan Model Pembelajaran Predict Observe Explain (POE) Untuk Meningkatkan Hasil Belajar Peserta Didik Pada Materi Getaran Dan Gelombang Dikelas VIII SMP Negeri 9 Tidore Kepulauan - Abdurahim, Sumira (Program Studi Pendidikan Fisika STKIP Kie Raha Ternate, 2023)
Thesis. Supervised by Irawati Hi Malan an Endang Fitria. This research is a classroom action research with the aim of improving participant learning outcomes on vibration and wave material in class VIII SMP Negeri 9 Tidore Kepulauan through the Predict Observe Explain (POE) learning model. This research model uses the Kemmis & Mc PTK model. Hand. The sample results was class VIII SMP Negeri 9 Tidore Kepulauan. The results of the first cycle of reflection showed that the imlementation of learning by referring to the forst cyle of reflecction shwed that the implementation of learning by referring to the lesson plan went quite well but was not optimal because the students were not used to using the POE learning model, the students had participated passively, and the pertencage of complete learning outcomes had not reached 75%. In the second cycle of reflection, the learning activities using the POE model were running (POE) learning model could improve student learning outcomes on vibration and wave material in class VIII SMP Negeri 9 Tidore Islands.